P22-17 Cell mechanisms induced by doxorubicin-loaded UCNP@MSN nanoparticles with a thermos-responsive nanovalve in melanoma cells - P. Oskoei; L.-M. Keller; E. Anderson; F.E. Maturi; B. Rühle; U. Resch-Genger; A.L. Daniel-da-Silva; L.D. Carlos; H. Oliveira (Toxicology Letters, 2025)

Mit Designer-Enzymen zu Prozessen - Bettina M. Nestl; Bernd A. Nebel; Verena Resch; Martin Schürmann; Dirk Tischler (BIOspektrum, 2025)

P01-46 Effects of doxorubicin-loaded UCNP@MSN core-shell particles with a thermoresponsive nanovalve in melanoma cells - P. Oskoei; J. Nogueira; L.-M. Keller; E. Andresen; F.E. Maturi; B. Rühle; U. Resch-Genger; A.L. Daniel-da-Silva; L.D. Carlos; H. Oliveira (Toxicology Letters, 2024)

OS01-12 A computational toolbox supporting the development of Safe and Sustainable by Design chemicals and materials - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; T. Rydberg; M. Halling; C.L. Battistelli; E. Benfenati; C. Bossa; E. Bouman; É. Bourgé; M. Brouwer-Milovanovic; et al. (Toxicology Letters, 2024)

Governance of advanced materials: Shaping a safe and sustainable future - Monique Groenewold; Eric A.J. Bleeker; Cornelle W. Noorlander; Adriënne J.A.M. Sips; Margriet van der Zee; Robert J. Aitken; James H. Baker; Martine I. Bakker; Evert A. Bouman; Shareen H. Doak; Damjana Drobne; Verónica I. Dumit; et al. (NanoImpact, 2024)

Safety-by-design and engineered nanomaterials: the need to move from theory to practice - Benjamin D. Trump; Dalila Antunes; José Palma-Oliveira; Andrew Nelson; Alexandra Misci Hudecova; Elise Rundén-Pran; Maria Dusinska; Ignasi Gispert; Susanne Resch; Beatriz Alfaro-Serrano; Antreas Afantitis; Georgia Melagraki; et al. (Environment Systems and Decisions, 2024)
As the governance of engineered nanomaterials (ENMs) evolves, innovations in the prevention, mitigation, management, and transfer of risk shape discussion of how nanotechnology may mature and reach various marketplaces. Safety-by-Design (SbD) is one leading concept that, while equally philosophy as well as risk-based practice, can uniquely help address lingering uncertainties and concerns stemming from regulatory evaluation of ENM risk across worker, consumer, and environmental safety. This paper provides a discussion on the SbD concept across different disciplines aiming to identify different approaches and needs to meet regulatory requirements—ultimately, we argue that SbD is evolving both to meet the needs and discourse of various disciplines, and to apply within differing marketplaces and national regulatory structures. Understanding how SbD has evolved within ENM can yield a more practical application and development of SbD, and help guide or unify national and international ENM governance around a core set of safety-driven principles.

Psychometric Properties of Computerized Cognitive Tools and Standard Neuropsychological Tests Used to Assess Sport Concussion: A Systematic Review - Kristin Wilmoth; Benjamin L. Brett; Natalie A. Emmert; Carolyn M. Cook; Jeffrey Schaffert; Todd Caze; Thomas Kotsonis; Margaret Cusick; Gary Solomon; Jacob E. Resch; C. Munro Cullum; Lindsay D. Nelson; et al. (Neuropsychology Review, 2023)

Accumulation mechanisms for contaminants on weak-base hybrid ion exchange resins - Sarah A. Saslow; Elsa A. Cordova; Nancy M. Escobedo; Odeta Qafoku; Mark E. Bowden; Charles T. Resch; Nabajit Lahiri; Emily T. Nienhuis; Daria Boglaienko; Tatiana G. Levitskaia; Peter Meyers; Jacqueline R. Hager; et al. (Journal of Hazardous Materials, 2023)

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Aldosterone-sensitive HSD2 neurons in mice - Silvia Gasparini; Jon M. Resch; Sowmya V. Narayan; Lila Peltekian; Gabrielle N. Iverson; Samyukta Karthik; Joel C. Geerling (Brain Structure and Function, 2019)

Respiratory syncytial virus-associated hospitalizations over three consecutive seasons in children with congenital heart disease - B. Resch; S. Kurath-Koller; J. Hahn; W. Raith; M. Köstenberger; A. Gamillscheg (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Behavioral assessment of acute inhibition of system xc - in rats - Victoria Lutgen; Jon Resch; Krista Qualmann; Nicholas J. Raddatz; Cristina Panhans; Ellen M. Olander; Linghai Kong; SuJean Choi; John R. Mantsch; David A. Baker (Psychopharmacology, 2014)

Perivascular cells of the supraspinatus tendon express both tendon- and stem cell-related markers - Herbert Tempfer; A. Wagner; R. Gehwolf; C. Lehner; M. Tauber; H. Resch; H. C Bauer (Histochemistry and Cell Biology, 2009)

CT-Operated Bifunctional Fluorescent Probe Based on a Pretwisted Donor–Donor–Biphenyl - Y. Q. Li; J. L. Bricks; U. Resch-Genger; M. Spieles; W. Rettig (Journal of Fluorescence, 2006)

Traceability in Fluorometry: Part II. Spectral Fluorescence Standards - U. Resch-Genger; D. Pfeifer; C. Monte; W. Pilz; A. Hoffmann; M. Spieles; K. Rurack; J. Hollandt; D. Taubert; B. Schönenberger; P. Nording (Journal of Fluorescence, 2005)

Large-scale lateral spreading and related mass movements in the Northern Calcareous Alps - J. Rohn; M. Resch; H. Schneider; T. M. Fernandez-Steeger; K. Czurda (Bulletin of Engineering Geology and the Environment, 2004)

Comparative analysis of satellite cell properties in heavy- and lightweight strains of turkey - F. Merly; C. Magras-Resch; T. Rouaud; J. Fontaine-Perus; M. F. Gardahaut (Journal of Muscle Research and Cell Motility, 1998)

Ammonia uptake and retention in some cyanobacteria - S. Boussiba; C. M. Resch; J. Gibson (Archives of Microbiology, 1984)

Rasche Carboxihmoglobinbestimmung mittels nichtdispersiver Ultrarot-Gasanalyse - H. Hauck; M. Neuberger; W. Resch (Archives of Toxicology, 1976)